Impact on dose distribution and volume changes of a bioabsorbable polyglycolic acid spacer during chemo-proton therapy for a pediatric Ewing sarcoma. (22nd September 2020) - Kimura, Mitsuhiro; Asai, Kumiko; Iwata, Hiromitsu; Ogino, Hiroyuki; Ito, Yasuhiko; Kamei, Michi; Takagi, Daisuke; Maeda, Naoko; Shibamoto, Yuta
ABSTRACT: The clinical utility of a recently developed bioabsorbable polyglycolic acid (PGA) spacer has not yet been established in pediatric patients; therefore, we aimed to investigate its utility during chemo-proton therapy for pediatric cancer. Proton depth–dose curves were obtained in a water phantom with or without the spacer. Computed tomography (CT) scans were performed for the PGA spacer immersed in saline for 2 weeks to measure CT numbers and estimate the relative stopping power (RSP) for the proton beams. The spacer was placed in a patient with sacral Ewing sarcoma receiving 55.8 Gy [relative biological effectiveness (RBE)] in 31 fractions and was evaluated using CT scans performed every other week. In addition, the images were used to quantitatively evaluate changes in volume and RSP of the spacer and dose distributions in normal tissues. The spacer immersed in saline had a CT number of 91 ± 7 (mean ± standard deviation) Hounsfield units, and the corresponding RSP was predicted to be 1.07 ± 0.01. The measured RSP agreed with the predicted one. The volumes of the large bowel and rectum receiving ≥45 Gy(RBE) (V45Gy ) were significantly reduced by placing the spacer; V45Gy without and with the spacer were 48.5 and 0.01%, respectively, for the rectum and 7.2 and 0%, respectively, for the large bowel. The volume of the spacer and RSP decreased at rates of 4.6 and 0.44% per week, respectively, whereas the target dose coverage was maintained until the end of treatment. The PGA spacer was considered effective for pediatric cancer patients undergoing chemo-proton therapy.